Niat Adopsi Generasi Z terhadap Solusi Pembayaran Digital FinTech - Candy, Candy; Budiman, Johny; Licca, Vellia; Oscar, Franky; Jolin, Jolin; Priscillia, Viviona (Universitas Bunda Mulia, 2025)
This study aims to address a research gap by comprehensively analyzing the interactions and contributions of performance expectancy, self-efficacy, and customer satisfaction to Generation Z’s behavioral intention to adopt FinTech-based digital payments. Data were collected through a questionnaire distributed to 198 respondents in Batam City from September to December 2024. The study employs the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, incorporating customer satisfaction as a mediating variable. The primary variables analyzed include performance expectancy, self-efficacy, customer satisfaction, and behavioral intention. Partial Least Squares Structural Equation Modeling (PLS-SEM), supported by SmartPLS software, was used for data analysis. The results indicate that performance expectancy significantly affects both customer satisfaction and behavioral intention, while self-efficacy significantly affects only customer satisfaction. Furthermore, customer satisfaction is shown to mediate the relationship between both performance expectancy and self-efficacy with behavioral intention.